Oral and aerosol immunization with viable or inactivated Actinobacillus pleuropneumoniae bacteria: antibody response to capsular polysaccharides in bronchoalveolar lavage fluids (BALF) and sera of pigs. - Hensel, A (1994)
To investigate the antibody response after local application of lung-pathogenic bacteria, pigs were immunized with viable or inactivated Actinobacillus pleuropneumoniae by the oral and aerogenous route. After 3 weeks class-specific immunoglobulins against purified A. pleuropneumoniae capsular polysaccharides (CP) were determined in serum and BALF by ELISA. A significant increase of IgA antibodies was found in BALF but not in sera of all immunized pigs. Oral immunization with viable A. pleuropneumoniae and aerosol immunization with either viable or inactivated bacteria resulted in a significant increase of IgG antibodies to the CP antigen in BALF, whereas only aerosol exposure to viable bacteria resulted in a significant increase in IgG antibodies in serum. A significant increase in anti-CP IgM in BALF was observed after aerosol exposure but not after oral immunization. IgM antibodies towards CP increased significantly by both routes of immunization with viable bacteria. The anti-CP activity of all three isotypes in sera and BALF was low in all groups compared with the positive controls, although inoculation of viable A. pleuropneumoniae led to higher levels of antibody concentration than inactivated bacteria. Our results indicate a traffic of primed lymphocytes from the gut into the bronchoalveolar airways and further support the hypothesis that polysaccharide-specific B cells may functionally mature at the mucosal surfaces.